Growth of Profit During and Post-pandemic (Covid 19): A Proposed Study - Duarti, Mega; ., Waluyo; ., Lestari (KnE Social Sciences, 2023)
The Covid-19 pandemic has caused significant changes for all manufacturing businesses listed on the Indonesia Stock Exchange. Therefore, the research aims to find out, analyze, and explore how return on assets, debt to equity, and net profit margin experienced differences before pandemic and during the Covid-19 pandemic. From a variety of empirical findings, there are still a limited number of studies that examine this during and after the Covid-19 pandemic. This research is expected to contribute to further research and facilitate the management of Indonesian manufacturing companies. In contrast, investors can provide information about the company’s financial performance. The importance of this research can be helpful for companies in providing solutions on how to increase profit growth after the Covid-19 pandemic. Keywords: return on asset, debt to equity, net profit margin, grow profit